Facile fabrication of silicon carbide decorated ceramic membrane, engineered with selective surface wettability for highly efficient separation of oil-in-water emulsions. Issue 2 (April 2023) - Baig, Umair; Waheed, Abdul; Dastageer, M.A.
Abstract: The separation of oil in water and water in oil emulsions using the ceramic membranes with selective oil and water wettability has proven to be cost effective, less cumbersome and more efficient, compared to the conventional methods. In this work, a silicon carbide having hexagonal crystal structure (H-SiC) based ceramic membrane, exhibiting in-air superhydrophilicity and underwater superoleophobicity was fabricated for water passing oil-water emulsion separation. Initially silicon dioxide (SiO2 ) was grown on the surface of H-SiC by thermal process to enhance the hydrophilicity, and further enhancement of hydrophilicity was introduced by amino-functionalizing H-SiC/SiO2 using N 1 -(3-trimethoxysilylpropyl)diethylenetriamine (N-TMS-DETA). The amino-functionalized H-SiC/SiO2 particles were deposited on porous alumina support surface and crosslinked via interfacial polymerization (IP) using Isophthaloyl chloride (IPC) cross-linker and ethylenediamine (EDA) to fabricate functional PA/H-SiC/SiO2 @Alumina ceramic membrane for oil/water emuslion separation. The morphological, structural, elemental characterizations using FT-IR, XRD, FE-SEM, EDS, elemental mapping, and the wettability of PA/H-SiC/SiO2 @Alumina ceramic membarne were carried out. The characterization results revealed the perfect deposition of functionalized H-SiC/SiO2 on alumina support surface, and the contact angles of PA/H-SiC/SiO2 @Alumina ceramic membrane surface in air-surface-water (θWA ), and oil-surface-water (θOW ) interfaces were 0° and ∼159.7° respectively. When PA/H-SiC/SiO2 @Alumina ceramic membrane was used for the oil-water emulsion separation using dead-end filtration cell, an impressive separation efficiency of > 99% with a flux of around 312 L∙m −2 ∙h −1 was observed. The system was tested for the separation efficiency at different transmembrane pressures, oil concentration of oil-water emulsion, and the long term stabilty of the PA/H-SiC/SiO2 @Alumina ceramic membrane. Graphical Abstract: ga1 Highlights: Formation of PA/H-SiC/SiO2 @Alumina ceramic membrane with unique surface wettability. The PA/H-SiC/SiO2 @Alumina ceramic membrane was applied for oily water treatment. The ceramic membrane was able to maintain a separation efficiency of > 99%. Current strategy of membrane fabrication shown to efficient for treating oily wastewater.